2022
DOI: 10.3390/toxics10030129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Term Biodegradable Film Mulch on Soil Physicochemical and Microbial Properties

Abstract: Biodegradable mulches have become the focus of attention, as pollution caused by leftover plastic mulch material becomes increasingly severe. However, the impact of biodegradable mulches to the soil needs to be further investigated. An experiment was conducted to evaluate the impact of no-mulch, biodegradable film mulch (BM) and polyethylene film mulch (PM) on the soil’s physical, chemical and biological properties after six years (2013–2019) of mulching in garlic growing season in a garlic-maize rotation. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…From the results, mulching with 15 cm Kachala grass performed better than the other treatments in improving the soil bulk density, which could be as a result of a better ground coverage by the Kachala grass coupled with higher mulching depth, which reduces the effect of compaction, caused by the impact of sprinkler water droplets. This is consistent with some studies such as [15,16,17] who have also shown that mulches can insignificantly improve the bulk density of soil. This indicates that using the mulches, especially Kachala grass with 15 cm depth as mulching material tends to improve the soil bulk density.…”
Section: Effects Of Mulching Regimes On Soil Bulk Densitysupporting
confidence: 92%
“…From the results, mulching with 15 cm Kachala grass performed better than the other treatments in improving the soil bulk density, which could be as a result of a better ground coverage by the Kachala grass coupled with higher mulching depth, which reduces the effect of compaction, caused by the impact of sprinkler water droplets. This is consistent with some studies such as [15,16,17] who have also shown that mulches can insignificantly improve the bulk density of soil. This indicates that using the mulches, especially Kachala grass with 15 cm depth as mulching material tends to improve the soil bulk density.…”
Section: Effects Of Mulching Regimes On Soil Bulk Densitysupporting
confidence: 92%
“…The use of such alternative materials has increased over the years. Several studies have demonstrated the advantages of the use of biopolymers over the use of standard synthetic polymers [ 6 , 9 , 10 , 11 ]. However, considering the limitations of biopolymers in terms of mechanical, chemical, and environmental resistance, the use of biomaterials may be restricted to only a few applications; most commonly mulching.…”
Section: General Overview Of Plastics Used In Agriculturementioning
confidence: 99%
“…As a more environmentally friendly alternative to traditional plastic mulches in agriculture, biodegradable mulch has grown in favour. Several agricultural activities, including managing weeds, retention of humidity, regulating temperatures, soil wellness, crop yield and quality, can benefit from the application of biodegradable mulch [13,7,14,15,16]. It may assist with control soil temperature, creating an environment that is conducive to plant growth, as well as can help maintain soil moisture, minimizing the need for treatment [13].…”
Section: Introductionmentioning
confidence: 99%
“…It may assist with control soil temperature, creating an environment that is conducive to plant growth, as well as can help maintain soil moisture, minimizing the need for treatment [13]. It can improve soil physicochemical and microbiological characteristics [14] and additionally encourage microbial activity and nutrient cycling [16]. It has the ability to boost agricultural yields and enhance crop quality [15].…”
Section: Introductionmentioning
confidence: 99%